STRATEGI INDONESIA MERAIH LISENSI LEGALITAS EKSPOR KAYU DALAM KERJASAMA PERJANJIAN FLEGT-VPA DENGAN UNI EROPA PERIODE 2007-2016 - Alvina Fidra, - (2018)
This research was conducted to distinguish the process of EU-Indonesia cooperation in wood exports to EU through FLEGT-VPA agreement 2007-2016 period. Indonesia began negotiations with the EU related to the prevalent handling of illegal logging in the wood export-import process, the negotiations began in 2007. Until 2013 Indonesia officially cooperates with the EU through FLEGT-VPA. The FLEGT form of cooperation established by the EU focuses on the trade policy of wood and wood products controlled by the European Union and purchases of wood and wood products carried out by the government and wood importers incorporated in member countries with logs into the process FLEGT must be legal with the inspection process by member states by meeting the main points of VPA which is legally-produced timber. In other words through FLEGT, the EU prioritizes the quality of incoming wood products in order to be legal and guaranteed by member countries, Indonesia in this case strives to meet the regulatory standards of the FLEGT agreement established by the European Union by establishing a timber legality verification system called SVLK, through a long process then in 2016 Indonesia became the first country in the world to get a legality license scheme by Forest Law Enforcement, Governance and Trade (FLEGT) for all exports of Indonesia wood products to 28 countries in the European Union. Using the concept of international cooperation and research diplomacy is expected to explain how Indonesia's process of achieving it as the first country to obtain a legality license granted by the European Union